Aplikasi Pemupukan Berimbang untuk Peningkatan Laju Pertumbuhan Tanaman Gaharu (Gyrinops verstegii) di Kabupaten Tabanan - SUSILA, KETUT DHARMA; MEGA, I MADE (Agrotrop : Journal on Agriculture Science; Vol 2 No 1 (2012), 2013)
The research that purposed to find out the combination dosage of balanced fertilizing between unorganic and organic fertilizers for growth rate increasing of gaharu was conducted at West Mundeh Village, West Selemadeg District and Baturiti Village Kerambitan District, Tabanan Regency from August 2006 until August 2007. The factorial experiment used was randomized block design consisted of two factors namely organic fertilizers as the first factor with four levels: 0 kg bokashi/tree; 2.5 kg bokashi/ tree; 5.0 Kg bokashi/tree; 7.5 kg bokashi/tree; and unorganic fertilizer (NPK fertilizers) as a second factor with four levels: without NPK; 0.10 kg NPK/tree; 0.20 kg NPK/tree, and 0.30 kg NPK/tree. There were 16 treatments with 4 replications. The result showed that no interaction between organic and unorganic fertilizer treatments, however, each factors influenced growth rate increasing of gaharu individually. Both organic (bokashi) and unorganic fertilizers (NPK) were increasing the stem diameters and hight of plants gaharu. Treatments of 0.30 kg NPK/tree and 7.5 kg bokashi/tree indicated better performance significantly for raising stem diameter than the others.
Keywords: Balanced fertilizing, growth rate of gaharu, organic and unorganic fertilizers